تطهير الملكية العقارية في التشريع الجزائري - محمد رضا حواسنية; عبد الحيكم مسلتي (My University, 2024)
Abstract: The subject of real estate property clearing in the Algerian legislation is considered one of the difficult and thorny topics that are being researched, as clearing real estate property aims to achieve a very precise knowledge of the property, by defining its legal nature, clearly defining its boundaries, and stating its area precisely, with a realistic determination of its location in the field. And a statement of the identity of its owners or possessors, whether private or public, and since the Algerian legislator adopted a set of legal mechanisms to contribute to the process and achieve comprehensive cleansing throughout the national territory, it was first necessary to get to know these mechanisms, which the general survey of the lands stipulated Pursuant to Order 75/74 of dated the 12/11/1975. is considered as a direct and basic mechanism for the process of comprehensive real estate property cleansing. The legislator also adopted other mechanisms that accelerate real estate cleansing and are more supportive of investment, which is the possession certificate, which was established in accordance with Article 39 of the Real Estate Guidance Law, as well as the property inspection procedure and the delivery of title deeds through a real estate investigation pursuant to Law 07/02 dated 02/27/2007. However, these mechanisms, when producing their effects, granted title deeds to the holders of unsurveyed real estate or possession deeds that enable their owner to exercise the right of exploitation and use over The real estate and its future possession through the statute of limitations did not achieve comprehensive real estate cleansing in the country and did not speed up the process as was hoped for, due to the disruption and delay of the public land survey works on the one hand, and on the other hand the danger of the possession certificate to the stability of the legal situation in the event of the emergence of The real owner of the property, as well as the ambiguity and difficulty of applying Law 07/02 related to real estate investigation and its lack of noticeable effect on accelerating the cleansing of real estate. ......................... الملخص: يعتبر موضوع تطهير الملكية العقارية في التشريع الجزائري من المواضيع الصعبة والشائكة التي يتم البحث فيها، حيث أن تطهير الملكية العقارية يهدف إلى تحقيق معرفة دقيقة جدا للعقار، من تحديد طبيعته القانونية و تعيين حدوده بشكل واضح وبيان مساحته بدقة، مع تحديد واقعي لموقعه في الميدان، وبيان لهوية مالكيه أو حائزيه سواء كانوا خواص أو عموميين، وحيث أن المشرع الجزائري اعتمد مجموعة من الآليات القانونية للمساهمة في استكمال العملية و تحقيق تطهير شامل في جميع التراب الوطني، كان لابد أولا من التعرف على هذه الآليات، التي يعتبر المسح العام للأراضي المنصوص عليه بموجب الأمر 75/74 المؤرخ في 12 نوفمبر 1975 آلية مباشرة وأساسية لعملية التطهير الشامل للملكية العقاري، كذلك اعتمد المشرع آليات أخرى مسرعة للتطهير العقاري وداعمة أكثر للاستثمار وهي شهادة الحيازة التي أنشئت بموجب المادة 39 من قانون التوجيه العقاري، وكذلك إجراء معاينة الملكية العقارية وتسليم سندات الملكية عن طريق تحقيق عقاري بموجب القانون 07/02 المؤرخ في 27/02/2007، غير أن هذه الآليات التي عند انتاج آثارها كانت تمنح سندات ملكية لحائزي العقارات غير الممسوحة أو سندات حيازية تمكن صاحبها من ممارسة حق الاستغلال والاستعمال على العقار وامتلاكه مستقبلا عن طريق التقادم المكسب، لم تحقق التطهير العقاري الشامل في البلاد ولم تسرع من العملية كما كان مرجوا منها، بسبب تعطل أشغال المسع العام للأراضي وتأخرها من جهة، ومن جهة أخرى خطورة شهادة الحيازة على استقرار الأوضاع القانونية في حال ضهور المالك الحقيقي للعقار، وكذلك غموض وصعوبة تطبيق القانون 07/02 المتعلق بالتحقيق العقاري وعدم انتاج آثاره بشكل ملحوظ على تسريع تطهير العقارات. ................................. Résumé : Le nettoyage des biens immobiliers dans la législation algérienne est l’un des sujets difficiles et épineux à l’étude. propriété ", puisque le nettoyage de l’immobilier vise à obtenir une connaissance très précise de la propriété, De déterminer sa nature juridique et de délimiter clairement ses limites et d’indiquer avec précision sa taille avec une identification réaliste de son emplacement sur le terrain et une identification de ses propriétaires ou titulaires, qu’ils soient privés ou publics et, depuis que le législateur algérien a adopté un ensemble de mécanismes juridiques pour contribuer à l’achèvement du processus et réaliser un nettoyage complet dans tous les territoires nationaux, ces mécanismes, qui sont l’arpentage général prévu par l’ordonnance n. 75/74 du 12 novembre 1975, Le législateur a également adopté d’autres mécanismes accélérés de dédouanement immobilier qui sont plus favorables à l’investissement, à savoir le certificat d’acquisition établi en vertu de l’article 39 de la loi sur la directive foncière ainsi que l’inspection des biens immobiliers et la délivrance du titre par une enquête immobilière en vertu de la loi 07/02 du 27/02/2007, mais ces mécanismes, lors de la production de leurs effets, L’octroi du titre de propriété aux détenteurs de biens sans papiers ou d’obligations d’acquisition permettant au propriétaire d’exercer le droit d’exploiter et d’utiliser le bien et de le posséder à l’avenir par une loi lucrative de prescription Développement, n’a pas obtenu une autorisation immobilière complète dans le pays et n’a pas accéléré le processus comme souhaité, en raison de la perturbation et du retard dans les travaux de la dotation foncière générale, d’une part, et d’autre part, le danger du certificat d’acquisition pour la stabilité des conditions juridiques en cas d’apparition du propriétaire réel, d’autre part, l’imprécision et la difficulté d’application de la loi 07/02 sur l’enquête immobilière et l’absence significative de production de ses effets sur l’accélération du nettoyage des propriétés.